2014
DOI: 10.1371/journal.pone.0084252
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Impact of Cambodia's Ancient City of Mahendraparvata (Phnom Kulen)

Abstract: The Khmer kingdom, whose capital was at Angkor from the 9th to the 14th-15th century, was founded in 802 by king Jayavarman II in a city called Mahandraparvata, on Phnom Kulen. Virtually nothing more is known of Mahandraparvata from the epigraphic sources, but systematic archaeological survey and excavation have identified an array of cultural features that point to a more extensive and enduring settlement than the historical record indicates. Recent remote sensing data have revolutionized our view, revealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
(24 reference statements)
2
20
0
Order By: Relevance
“…This suggests a long and complex history for Mahendraparvata following its late eighth- to early ninth-century tenure as a capital, involving periods of renovation and transformation. These, in turn, accord with inscriptions that attest to the continued use of Phnom Kulen as a site of worship and pilgrimage throughout the Angkor period (Chevance 2013, 2014), and also with local palaeobotanical records suggesting extensive and intensive human land use from the eighth to twelfth centuries AD (Penny et al 2014).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This suggests a long and complex history for Mahendraparvata following its late eighth- to early ninth-century tenure as a capital, involving periods of renovation and transformation. These, in turn, accord with inscriptions that attest to the continued use of Phnom Kulen as a site of worship and pilgrimage throughout the Angkor period (Chevance 2013, 2014), and also with local palaeobotanical records suggesting extensive and intensive human land use from the eighth to twelfth centuries AD (Penny et al 2014).…”
Section: Discussionsupporting
confidence: 73%
“…To address this lacuna in the archaeology of Angkor, we undertook intensive survey and excavation programmes on Phnom Kulen in order to understand the spatial and chronological dimensions of Angkor-period occupation (Chevance 2011, 2013, 2014, 2015; Penny et al 2014). The development of archaeological maps has been enhanced considerably by the application of airborne laser scanning (lidar) techniques in two separate campaigns: the first in 2012, by the Khmer Archaeology LiDAR Consortium, and another in 2015, by the Cambodian Archaeological Lidar Initiative (Evans et al .…”
Section: Introductionmentioning
confidence: 99%
“…, Clement et al 125 130 . 131 have shown that the area that our figure shows was subject to intensive land use for several centuries between the 8 th and 12 th centuries CE, punctuated by episodes of severe erosion.…”
Section: Acknowledgmentsmentioning
confidence: 68%
“…Until recently the structure of this city was very poorly defined; however, the 2012 ALS campaign suddenly brought the urban network into very sharp relief, as well as adding insights into the level of Angkor-era deforestation and the sustainability of its water management infrastructure Penny et al, 2014). It was suspected, however, that the 2012 campaign had captured only a subset of a much more extensive urban network on Phnom Kulen.…”
Section: Beng Mealea Phnom Kulen and Northern Angkormentioning
confidence: 99%